2011
DOI: 10.2147/ceg.s24093
|View full text |Cite
|
Sign up to set email alerts
|

Maspin is a deoxycholate-inducible, anti-apoptotic stress-response protein differentially expressed during colon carcinogenesis

Abstract: Increased maspin expression in the colon is related to colon cancer risk and patient survival. Maspin is induced by the hydrophobic bile acid, deoxycholate (DOC), which is an endogenous carcinogen and inducer of oxidative stress and DNA damage in the colon. Persistent exposure of colon epithelial cells, in vitro, to high physiologic levels of DOC results in increased constitutive levels of maspin protein expression associated with the development of apoptosis resistance. When an apoptosis-resistant colon epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Experimental studies show that high Maspin expression is correlated with increased apoptosis resistance in CRC cells (Payne et al , 2011). Furthermore, it has been shown that circulating tumour cells in peripheral blood of CRC patients express high levels of Maspin (Findeisen et al , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies show that high Maspin expression is correlated with increased apoptosis resistance in CRC cells (Payne et al , 2011). Furthermore, it has been shown that circulating tumour cells in peripheral blood of CRC patients express high levels of Maspin (Findeisen et al , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Both deficiency of CcOI and increased Maspin protein expression appear to cause apoptosis resistance, as reviewed for CcOI by Bernstein et al [ 12 ], and shown for Maspin by Payne et al [ 61 ]. Immunohistochemical evaluations were made for deficiency of cytochrome coxidase subunit I (CcOI) [ 12 ] or increased expression of Maspin [ 61 ] in colonic epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Both deficiency of CcOI and increased Maspin protein expression appear to cause apoptosis resistance, as reviewed for CcOI by Bernstein et al [ 12 ], and shown for Maspin by Payne et al [ 61 ]. Immunohistochemical evaluations were made for deficiency of cytochrome coxidase subunit I (CcOI) [ 12 ] or increased expression of Maspin [ 61 ] in colonic epithelium. These evaluations were made in tissues from biopsies of patients with no history of colonic neoplasia, from tissue samples taken from resections 1-10 cm distant from colon cancers, tissues at the margins of cancers and tissue samples within cancers (and for Maspin, also within adenomas).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Progression to colon cancer proceeds by means of numerous changes in the colonic mucosa, progressing from normal tissue to "field defects" in the non-neoplastic flat mucosa, to hyperplastic polyps, to adenomatous polyps (adenomas), and, ultimately, to colon cancer 18 .…”
Section: Secondary Bile Acids In Mice: Intake Dose In Food Vs Level mentioning
confidence: 99%